2021
DOI: 10.3389/fnsys.2021.726403
|View full text |Cite
|
Sign up to set email alerts
|

The Shared Origins of Embodiment and Development

Abstract: As a domain of study centering on the nature of the body in the functioning of the individual organism, embodiment encompasses a diverse array of topics and questions. One useful organizing framework places embodiment as a bridge construct connecting three standpoints on the body: the form of the body, the body as actively engaged in and with the world, and the body as lived experience. Through connecting these standpoints, the construct of embodiment shows that they are not mutually exclusive: inherent in for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…This idea means that an individual's development is embodied in the tripartite manner presented by Overton (2008Overton ( , 2015 and so resolves the question of how the developmental system can, in itself, be self-constructive, or autopoietic. Indeed, the view of Marshall et al (2021) is consistent with Witherington's (2014) idea that tripartite integration of processes involving the morphological and physiological dimension of embodiment, the self (psychological and behavioral) dimension of embodiment, and the sociocultural dimension of embodiment enables each individual to serve "as its own cause, organizing and DOI: 10.1159/000521583 producing itself such that it causes and results from itself. In this way, living systems constitute natural ends or purposes" (p. 27).…”
Section: Conceptual and Methodological Issues In Understanding The Em...supporting
confidence: 59%
See 2 more Smart Citations
“…This idea means that an individual's development is embodied in the tripartite manner presented by Overton (2008Overton ( , 2015 and so resolves the question of how the developmental system can, in itself, be self-constructive, or autopoietic. Indeed, the view of Marshall et al (2021) is consistent with Witherington's (2014) idea that tripartite integration of processes involving the morphological and physiological dimension of embodiment, the self (psychological and behavioral) dimension of embodiment, and the sociocultural dimension of embodiment enables each individual to serve "as its own cause, organizing and DOI: 10.1159/000521583 producing itself such that it causes and results from itself. In this way, living systems constitute natural ends or purposes" (p. 27).…”
Section: Conceptual and Methodological Issues In Understanding The Em...supporting
confidence: 59%
“…Therefore, the data sets available about the description, explanation, or optimization of positive character processes within self-system processes are not able to fully contribute to a thorough appraisal of the autopoietic facet of the dynamic developmental system. In other words, there are not fully embodied data sets pertinent to the contributions of positive character development processes in the illumination of the RDS-based idea that "living things actively self-maintain themselves through the constant regeneration of the conditions that are necessary to sustain their material existence" (Marshall et al, 2021, p. 3)… [and thus reflect] "constitutive autonomy… in contrast to behavioral autonomy, where the identity of the system is imposed externally by an operator or observer" (Marshall et al, 2021, p. 4).…”
Section: Conceptual and Methodological Issues In Understanding The Em...mentioning
confidence: 99%
See 1 more Smart Citation
“…The girls who were interviewed described dance and yoga as fun physical activities; they observed that dance brought a sense of happiness while yoga, especially the relaxation element, facilitated calmness. These experiences show that both activities influenced the girls' minds and emotions, which is what the theory of embodiment is about (39,40). One girl explained dancing made her stronger and therefore it felt better inside.…”
Section: Discussionmentioning
confidence: 70%
“…A recent meta-analysis showed that interventions based on SDT led to improvements on indices of health and STD constructs (38). The JiT intervention was based on the theory of embodiment, which implies that the motor system and the cognitive affective system are intertwined and therefore influence each other (39)(40)(41). Each dance and yoga group consisted of between 7 and 14 girls and was led by a trained dance and yoga instructor (or sometimes two instructors together), who also had previous experience of working with children.…”
Section: Participants and Settingmentioning
confidence: 99%